2009
DOI: 10.3345/kjp.2009.52.4.453
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of acute noroviral gastroenteritis in children : comparison with rotaviral gastroenteritis

Abstract: Re s u l t s: In the norovirus group, 19 (86.4%) children showed vomiting and 21 (95.5%) children showed diarrhea, while all children in the rotaviral group showed both vomiting and diarrhea. The duration of vomiting was not different in the two groups, but mean episodes of vomiting/24 h were higher in the norovirus group than in the rotavirus group. The duration of diarrhea was longer and mean episodes of diarrhea/24 h were higher in the rotavirus group. The Vesikari Scale was not different in the two groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
5
7
0
Order By: Relevance
“…This result corresponds with previous studies that have demonstrated the similar symptoms of noroviral and rotaviral gastroenteritis, and that noroviral gastroenteritis has a milder course [20][21][22]. Leukocytosis (55.0%) and lymphocytosis (21.0%) were more frequently observed in the norovirus-infected group than in the rotavirus-infected group, again matching findings from a previous study [23]. For noroviral gastroenteritis cases, the clinical symptoms were milder than the laboratory findings.…”
Section: Discussionsupporting
confidence: 80%
“…This result corresponds with previous studies that have demonstrated the similar symptoms of noroviral and rotaviral gastroenteritis, and that noroviral gastroenteritis has a milder course [20][21][22]. Leukocytosis (55.0%) and lymphocytosis (21.0%) were more frequently observed in the norovirus-infected group than in the rotavirus-infected group, again matching findings from a previous study [23]. For noroviral gastroenteritis cases, the clinical symptoms were milder than the laboratory findings.…”
Section: Discussionsupporting
confidence: 80%
“…Hwang et al8) also reported leukocytosis in 4 cases (18.2%) of norovirus infection and 4 cases (8.9%) of rotavirus infection. Abnormal liver function test results were also observed in 14 cases (63.6%) of norovirus infection and 40 cases (88.9%) of rotavirus infection.…”
Section: Discussionmentioning
confidence: 93%
“…The signs and symptoms of norovirus infection were relatively mild compared to rotavirus infection. Hwang et al8) reported that mean duration of hospitalization was 3.9 and 4.2 days for rotavirus and norovirus infections, respectively and no significant differences were noticed in the frequency and duration of vomiting in these gastroenteritis. In our study, the difference in the mean duration of diarrhea between rotaviral (4.8 days) and noroviral (6.8 days) infections was statistically significant.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Consistent with previous studies, clinical presentation of patient with AGE is not generally indicative of a pathogen. It has been reported that symptoms, the length of hospitalization, and the number of diarrhea episodes are not significantly different for the different infectious agents [27,33,36].…”
Section: Discussionmentioning
confidence: 98%